First report of ergot caused by Claviceps clavispora in switchgrass (Panicum virgatum L.) in Georgia, USA - Rijal, Samikshya (Plant disease, 2024)
Switchgrass (Panicum virgatum L.) is a North American grass species with biofuel potential. Claviceps spp. is known to infect the florets of various grass species, initially characterized by a sticky honeydew exudate and later as sclerotium replacing the seed in the infected ovary (Tanaka et al 2023). Since 2019, from July to October, switchgrass panicles in Georgia have been observed with honeydew and black sclerotia. The disease was first noted on some of the 285 accessions of the genome-wide association study (GWAS) panels at the University of Georgia's Iron Horse Farm in Watkinsville and Gibbs Farm in Tifton, GA. In Watkinsville, GA, ergot incidence was 5%, 6%, 65% and 54% in 2019, 2020, 2021 and 2022, respectively. Symptomatic panicles with honeydew and sclerotia were collected in 2021 (sample Scl) and 2023 (samples Cla_M and ATH20cl) from Watkinsville, GA. Under microcopy, panicles with honeydew symptoms had mycelium and conidia (9 μm long [range of 5-13 μm] and 4 μm wide [3-5 μm]) consistent with Claviceps spp. (Tooley et al. 2001). Sclerotia were 1.5 mm long (range 1-3 mm). Sclerotia were surface sterilized for 3 minutes in 5% NaOCl, followed by 70% ethanol then rinsed three times in distilled water. Sterilized sclerotia were plated on potato dextrose agar and placed on bench top with a 12-hour day/night cycle at room temperature (22°C) (Singh 1976). After 2 months, the sclerotia produced sterile apothecia. For molecular identification, genomic DNA was extracted from three honeydew samples following the protocol of Doyle and Doyle (1987). The internal transcribed spacer (ITS) region and RNA polymerase second largest subunit (RPB2) gene were amplified using ITS4/ITS5 (White et al. 1990) and 5F2/7CR (Liu et al. 1999) primer sets. The ITS region of ATH20cl, Cla_M, and Scl (GenBank nos. PP546317- PP546319) showed 92.83-97.48% identity to C. clavispora (NR_163506.1). The RPB2 region of ATH20cl, Cla_M, and Scl (GenBank nos. PP573916- PP573918) showed 97.46-97.72% identity to C. clavispora (LT216566.1). The maximum likelihood tree constructed in MEGA-X (Kumar et al. 2018) using concatenated ITS (539 bp) and RPB2 (792 bp) gene sequences from this study and eleven reference sequences from Tanaka et al. (2023), revealed close relatedness of ATH20cl, Cla_M, and Scl to C. clavispora under section Pusillae. The pathogenicity test for samples ATH20cl and Cla_M was conducted in the greenhouse on switchgrass cultivar 'Alamo' grown in injection molded pots containing Sungro professional growing mix. Three replicates plants at reproductive (R3) growth stage were inoculated by immersing panicles in 105 spores/ml suspension for 5 minutes and bagged for 3 days (Tooley et al. 2001). Control plants were immersed in distilled water. Honeydew symptoms and sclerotia appeared within 7- and 90-days post-inoculation, respectively, whereas control plants remained symptom-free. The honeydew collected from the infected Alamo panicles were reconfirmed to produce similar spores to those collected from the field. This is the first report of ergot caused by C. clavispora in switchgrass. Ergot was also observed since 2019 on some accessions from the same GWAS panel planted at the University of Tennessee Plant Sciences Farm in Knoxville, TN. This information will be beneficial to determine the effect of ergot on biomass production and seed quality of switchgrass in the southeastern U.S